Impact of microbial processes on the safety of deep geological repositories for radioactive waste - Ruiz-Fresneda, Miguel A.; Martinez-Moreno, Marcos F.; Povedano-Priego, Cristina; Morales-Hidalgo, Mar; Jroundi, Fadwa; Merroun, Mohamed L. (Frontiers in Microbiology, 2023)
To date, the increasing production of radioactive waste due to the extensive use of nuclear power is becoming a global environmental concern for society. For this reason, many countries have been considering the use of deep geological repositories (DGRs) for the safe disposal of this waste in the near future. Several DGR designs have been chemically, physically, and geologically well characterised. However, less is known about the influence of microbial processes for the safety of these disposal systems. The existence of microorganisms in many materials selected for their use as barriers for DGRs, including clay, cementitious materials, or crystalline rocks (e.g., granites), has previously been reported. The role that microbial processes could play in the metal corrosion of canisters containing radioactive waste, the transformation of clay minerals, gas production, and the mobility of the radionuclides characteristic of such residues is well known. Amongst the radionuclides present in radioactive waste, selenium (Se), uranium (U), and curium (Cm) are of great interest. Se and Cm are common components of the spent nuclear fuel residues, mainly as 79Se isotope (half-life 3.27 x 105 years), 247Cm (half-life: 1.6 x 107 years) and 248Cm (half-life: 3.5 x 106 years) isotopes, respectively. This review presents an up-to-date overview about how microbes occurring in the surroundings of a DGR may influence their safety, with a particular focus on the radionuclide-microbial interactions. Consequently, this paper will provide an exhaustive understanding about the influence of microorganisms in the safety of planned radioactive waste repositories, which in turn might improve their implementation and efficiency